2019
DOI: 10.3390/atmos11010005
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Control of Water-Soluble Inorganic Ions in PM2.5 from Nanning, a Subtropical Monsoon Climate City in Southwestern China

Abstract: In this study, we measured the daily water-soluble inorganic ions (WSIIs) concentration (including SO42−, NO3−, NH4+, Ca2+, K+, Cl−, Na+, Mg2+, and F−) of PM2.5 (particulate matter with a diameter smaller than 2.5 μm) throughout the year in Nanning (a typical subtropical monsoon climate city in southwestern China) to explore the influence of seasonal climate change on the properties of PM2.5 pollution. This suggested that SO42−, NO3−, and NH4+ were the main component of WSIIs in Nanning. Secondary inorganic io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…PM 2.5 has been widely studied in recent years in China due to its potential impacts on air quality and human health. Water-soluble inorganic ions (WSIIs), organic carbon (OC) particles, inorganic carbon (EC) particles, and inorganic elements (IEs), as the main chemical components of PM 2.5 , have been extensively studied in China [7][8][9]. WSIIs are dominated by secondary inorganic aerosols (SIAs), including NH 4 + , NO 3 − , and SO 4 2− .…”
Section: Introductionmentioning
confidence: 99%
“…PM 2.5 has been widely studied in recent years in China due to its potential impacts on air quality and human health. Water-soluble inorganic ions (WSIIs), organic carbon (OC) particles, inorganic carbon (EC) particles, and inorganic elements (IEs), as the main chemical components of PM 2.5 , have been extensively studied in China [7][8][9]. WSIIs are dominated by secondary inorganic aerosols (SIAs), including NH 4 + , NO 3 − , and SO 4 2− .…”
Section: Introductionmentioning
confidence: 99%
“…winter, cluster 3 in spring and cluster 3 in summer). However, the emissions of gaseous precursors (NO2 and SO2, no data for NH3) in these areas are close to Guiyang, such as Kunming and Nanning [21,41]. Thus, lower SNA concentrations were found in some trajectories, which could be ascribed to these trajectories that reflected long-distance air transport and were fast-moving, so the pollutants may not easily be enriched in these trajectories [58,59].…”
Section: The Corresponding Concentrations Of Speciesmentioning
confidence: 95%
“…Previous studies have shown that the contaminants from fossil fuel combustion, agricultural incineration, and automobile emissions account for more than 60% of the PM 2.5 concentration. (33) Autumn and winter are the periods of heating in northern cities. PM 2.5 pollutants released from fossil fuel combustion into the air increase nearly sevenfold during this period, directly leading to a significant increase in PM 2.5 concentration in autumn and winter.…”
Section: Modeling Accuracymentioning
confidence: 99%